Liraglutide as a treatment option for weight regain after laparoscopic sleeve gastrectomy in patients with obesity and higher anaesthesiologist risk - Martines, Gennaro; Tomasicchio, Giovanni; Rotelli, Maria Teresa; De Fazio, Michele (Frontiers in Surgery, 2025)
BackgroundThe underlying causes of weight regain remain largely unclear, and well-defined treatment options are lacking. This retrospective study seeks to assess the effectiveness of liraglutide in managing weight regain among patients with elevated anesthesiology risks who underwent laparoscopic sleeve gastrectomy (LSG) as their primary surgical procedure.MethodsClinical records of patients with obesity from January 2017 to January 2024 were retrospectively analysed. Patients with elevated anesthesiology risks who experienced weight regain following LSG and treated with liraglutide 3.0 mg, contingent upon their completion of a follow-up period of six months were included. Demographic data, pre-operative and post-treatment weight, Body Mass Index (BMI), and total weight loss percentage (%TWL) were recorded at the third and sixth months of follow-up.ResultsForty patients managed weight regain with liraglutide. All patients had an ASA score of 3 and had at least one comorbidity. Pre-treatment weight and BMI were observed at 91 kg and 33.6 kg/m2, indicating a marked reduction, with a %TWL of 10.5%. At the 3-month, the median weight decreased to 82 kg, with the BMI at 31 kg/m2; p < 0.005. At the conclusion of the 6-month, all patients achieved a median weight of 75 kg and a BMI of 28.7 kg/m2, demonstrating a significant decline from the 3-month measurements, with a %TWL of 27.5%.ConclusionLiraglutide, at a maximum dosage of 3.0 mg, has the potential to mitigate weight regain after LSG in patients who are not appropriate candidates for revisional surgery due to various comorbidities.